R Term of (A + B) Geometric Progression

Download as docx, pdf, or txt
Download as docx, pdf, or txt
You are on page 1of 1

rth term of (a + b)n Geometric Progression:

𝑛! 𝑎𝑛 = 𝑎1 𝑟 𝑛−1
𝑟 𝑡ℎ 𝑡𝑒𝑟𝑚 = 𝑎𝑛−𝑟+1 𝑏 𝑟−1
(𝑛 − 𝑟 + 1)! (𝑟 − 1)!
𝑎𝑛 (𝑟 𝑛 − 1)
𝑆=
𝑟−1
Coefficient of next term: Sum of infinite Geometric Progression:

(𝑐𝑜𝑒𝑓. 𝑜𝑓 𝑝𝑟𝑒𝑣 𝑡𝑒𝑟𝑚)(𝑒𝑥𝑝 𝑜𝑓 𝑥 𝑜𝑓 𝑝𝑟𝑒𝑣 𝑡𝑒𝑟𝑚) 𝑎1


𝐶= 𝑆=
(𝑒𝑥𝑝 𝑜𝑓 𝑦 𝑜𝑓 𝑝𝑟𝑒𝑣 𝑡𝑒𝑟𝑚) + 1 1−𝑟

Sum of coefficient of variables

Note: Substitute value of ‘1” to all variables. If


there is a term with no variable (x0), n, subtract
the value of n raised to expansion exponent.

Quadratic Formula:

−𝐵 ± √𝐵2 − 4𝐴𝐶
𝑥=
2𝐴
∆ = 𝐵2 − 4𝐴𝐶

If:

∆=0: Roots are equal

∆>0: Roots are real and unequal

∆<0: Roots are imaginary

Sum of roots:
𝐵
𝑥1 + 𝑥2 = −
𝐴
Product of roots:
𝐶
𝑥1 𝑥2 =
𝐴

Arithmetic Progression

𝑎𝑛 = 𝑎1 + (𝑛 − 1)𝑑
𝑛
𝑆= (𝑎 + 𝑎𝑛 )
2 1

You might also like